The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00702-012-0814-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of N-valproyl-l-tryptophan on high potassium, low calcium and low magnesium-induced CA1 hippocampal epileptiform bursting activity in rat brain slices

Abstract: N-valproyl-L-tryptophan (VPA-Tryp), new antiepileptic drug, was tested on CA1 hippocampal epileptiform bursting activity obtained by increasing potassium and lowering calcium and magnesium concentrations in the fluid perfusing rat brain slices. Each slice was treated with a single concentration (0.2, 0.5, 1 or 2 mM) of Valproate (VPA) or VPA-Tryp. Both burst duration and interburst frequency during and after treatment were off-line compared with baseline values. For both parameters, the latency and the length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The current results provide innovative evidence of the possible impact of microtubule cytoskeleton on hyperexcitability-based diseases. Noticeably, our experimental design exploiting two drug-free models of epileptiform activity (Stringer and Lothman, 1992 ; Sardo et al, 2012 ) allowed us to evaluate the results in an intact neuronal network, but also to exclude the influence of blood-brain barrier (BBB; Jefferys and Haas, 1982 ) and to appreciate whether any effect directly influenced hippocampal neurons. In this context, some molecular studies previously reported that, in kainate (KA)-induced epileptic state, altered microtubule formation contributed to aberrant neurogenesis in the DG with an increase in the gene expression of tubulin and microtubule-associated proteins (Represa et al, 1993 ; Pollard et al, 1994 ; Hendriksen et al, 2001 ; Sato and Abe, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current results provide innovative evidence of the possible impact of microtubule cytoskeleton on hyperexcitability-based diseases. Noticeably, our experimental design exploiting two drug-free models of epileptiform activity (Stringer and Lothman, 1992 ; Sardo et al, 2012 ) allowed us to evaluate the results in an intact neuronal network, but also to exclude the influence of blood-brain barrier (BBB; Jefferys and Haas, 1982 ) and to appreciate whether any effect directly influenced hippocampal neurons. In this context, some molecular studies previously reported that, in kainate (KA)-induced epileptic state, altered microtubule formation contributed to aberrant neurogenesis in the DG with an increase in the gene expression of tubulin and microtubule-associated proteins (Represa et al, 1993 ; Pollard et al, 1994 ; Hendriksen et al, 2001 ; Sato and Abe, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of drug administration, slices were again perfused with drug-free modified aCSF for 10 min (wash-out period). The duration and dosages of administration were chosen taking into consideration previous studies on these drugs, the reported equilibration time course of other antiepileptic drugs and pilot experiments in hippocampal slices at the depth of recording (Furukawa and Mattson, 1995 ; Petrini et al, 2004 ; Puthanveettil et al, 2008 ; Sardo et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, indicaxanthin released from a barrel in 5 min at 60 nA was equivalent to 0.1 μl, corresponding approximatively to 0.34 ng (for 12 μM), 0.17 ng (for 6 μM), and 0.085 ng (for 3 μM). Apart from brain localization, microiontophoretic recordings were carried out in telencepahalic and diencephalic regions (cortex, hippocampus, striatum, globus pallidus, thalamus and subthalamic nucleus), involved in cognitive processes and mostly investigated by our group in previous electrophysiological researches (Sardo et al, 2003 , 2006 , 2009 , 2012 ; Carletti et al, 2012 , 2017 ; Plescia et al, 2014 ). Hindbrain areas were not taken in consideration for recordings because of stereotaxic limitations.…”
Section: Methodsmentioning
confidence: 99%
“…In most of the neurological therapies, including Parkinson's disease, schizophrenia and depression, the prodrugs generally improve the efficacy of the parent drug thus decreasing the systemic and/or unwanted tissue/organspecific toxicity. Chemical manipulation of dopaminergic drugs could afford derivatives that, following bioactivation, are able to selectively bind the brain dopamine receptor subtypes, resulting thus in balance modulation of dopaminergic transmission [1][2][3].…”
Section: Introductionmentioning
confidence: 99%